Papua New Guinea food price bulletin: October 2025 - International Food Policy Research Institute; Hayoge, Glen; Kedir Jemal, Mekamu (International Food Policy Research Institute, 2025)
This report provides analysis of food price trends for the third quarter (Q3) of 2025, from July to September. The Fresh Produce Development Agency (FPDA) continues to collect prices from major markets despite recurrent logistical challenges to maintain consistent data for capturing, analyzing and informing relevant stakeholders. Due to insufficient data being collected from April to June (collected only for May across all markets and for April in Banz and Kokopo), no second quarter bulletin was published. This report compares prices in Q3 2025 with Q1, Q2 (with the available limited data) of 2025, and Q3 2024 to identify quarterly and year-on-year trends of prices. Prices are reported in PGK per kilogram and represent real prices adjusted for inflation using FAO Consumer Food Price Index (PCI) and price gaps (April to September 2025) filled using a growth rate calculated from the PNG National Statistical Office (NSO) - June quarterly PCI data. This bulletin focuses on selected important staples (sweet potato, taro, cassava, cooking banana and rice), vegetables (aibika, English cabbage, capsicum, carrot, and choko-tips) and fruits (lemon, orange, pawpaw and pineapple). For longer time series data and interactive tools, visit the IFPRI website and download food price data here.